The ethics of human systems : creating economic value with impact for good - Pretel-Wilson, Manel (Routledge, 2026)
Addressing major social and ecological issues, this book establishes the field of ethics as a fundamental science that cannot be separated from economics and business. In particular, it redefines the nature of good investments which, besides being profitable, have to realize values as opposed to reinforcing the countervalues that are destroying our world.The book develops a universal morality hypothesis constituted by four sets of universal values-countervalues that correspond to the fundamental laws of ethics. This new understanding of ethics makes human systems the architects that can save our world through doing something for others that satisfies need rather than greed. This book argues that we can realize values through providing something of value to others, that is, human systems can create economic value with impact for good.The Ethics of Human Systems is an insightful read for academics and practitioners in the fields of systems thinking, business ethics, and impact investing in particular.
Keywords: Ethics.; Interpersonal relations.; Social ethics.; Social psychology.; elektronické knihy; electronic books